Does anyone read my papers? The gap between academic consumer research and the real (wine) world - Riccardo Vecchio (Wine Economics and Policy, 2023)
The goal of this discussion paper is to foster the debate among scholars on some of the key issues that are currently challenging the impact of academic wine consumer studies and encourage younger researchers towards alternative paths. Based on my personal experience, I will focus on some scholars' practices that (in my view) could be revised to increase the reconnection of researchers to the practical world, namely: topic relevance Vs. trendiness, methodological approaches and data utility, sample issues and the replication crisis.
Keywords: 330; scholars; relevance; practicioners